Corpos, vestuário e estrutura social : a arte germânica da iluminura no Codex Manesse (século XIII) - Pereira, Beatriz Passamai (2018)
This research investigated the clothing of the ministerial knights in the Große Heidelberger Liederhandschrift with the aim of capturing the reflections of the medieval social order of the thirteenth century based on the miniature ilustraions present in t